A new translation and reader's guide to Victor von Ebner's classical description of spermatogenesis. Issue 11 (22nd October 2019) - Jones, Susanne L.; Harris, Katya; Geyer, Christopher B.
Abstract : This is a translation and modern interpretation of one of the most important manuscripts on spermatogenesis, published by Victor von Ebner, in 1871. It was originally written in Italian, and to the best of my knowledge has never been translated to English or examined by modern scientists.